A comparison of clinical outcomes, service satisfaction and well-being in people using acute day units and crisis resolution teams: cohort study in England. Issue 2 (19th March 2021) - Lamb, Danielle; Steare, Thomas; Marston, Louise; Canaway, Alastair; Johnson, Sonia; Kirkbride, James B.; Lloyd-Evans, Brynmor; Morant, Nicola; Pinfold, Vanessa; Smith, Deb; Weich, Scott; Osborn, David P.
Abstract : Background: For people in mental health crisis, acute day units (ADUs) provide daily structured sessions and peer support in non-residential settings, often as an addition or alternative to crisis resolution teams (CRTs). There is little recent evidence about outcomes for those using ADUs, particularly compared with those receiving CRT care alone. Aims: We aimed to investigate readmission rates, satisfaction and well-being outcomes for people using ADUs and CRTs. Method: We conducted a cohort study comparing readmission to acute mental healthcare during a 6-month period for ADU and CRT participants. Secondary outcomes included satisfaction (Client Satisfaction Questionnaire), well-being (Short Warwick–Edinburgh Mental Well-being Scale) and depression (Center for Epidemiologic Studies Depression Scale). Results: We recruited 744 participants (ADU: n = 431, 58%; CRT: n = 312, 42%) across four National Health Service trusts/health regions. There was no statistically significant overall difference in readmissions: 21% of ADU participants and 23% of CRT participants were readmitted over 6 months (adjusted hazard ratio 0.78, 95% CI 0.54–1.14). However, readmission results varied substantially by setting. At follow-up, ADU participants had significantly higher Client Satisfaction Questionnaire scores (2.5, 95% CI 1.4–3.5, P < 0.001) and well-being scores (1.3, 95% CI 0.4–2.1, P = 0.004), and lower depression scores (−1.7, 95% CI −2.7 to −0.8, P < 0.001), than CRT participants. Conclusions: Patients who accessed ADUs demonstrated better outcomes for satisfaction, well-being and depression, and no significant differences in risk of readmission, compared with those who only used CRTs. Given the positive outcomes for patients, and the fact that ADUs are inconsistently provided in the National Health Service, their value and place in the acute care pathway needs further consideration and research.